DNA methylation analyses of the candidate genes identified by a methylome‐wide association study revealed common epigenetic alterations in schizophrenia and bipolar disorder. Issue 4 (11th March 2018) - Sugawara, Hiroko; Murata, Yui; Ikegame, Tempei; Sawamura, Rie; Shimanaga, Shota; Takeoka, Yusuke; Saito, Takeo; Ikeda, Masashi; Yoshikawa, Akane; Nishimura, Fumichika; Kawamura, Yoshiya; Kakiuchi, Chihiro; et al.
Abstract : Aim: Schizophrenia (SZ) and bipolar disorder (BD) have been known to share genetic and environmental risk factors, and complex gene–environmental interactions may contribute to their pathophysiology. In contrast to high genetic overlap between SZ and BD, as revealed by genome‐wide association studies, the extent of epigenetic overlap remains largely unknown. In the present study, we explored whether SZ and BD share epigenetic risk factors in the same manner as they share genetic components. Methods: We performed DNA methylation analyses of the CpG sites in the top five candidate regions ( FAM63B, ARHGAP26, CTAGE11P, TBC1D22A, and intergenic region [IR] on chromosome 16) reported in a previous methylome‐wide association study (MWAS) of SZ, using whole blood samples from subjects with BD and controls. Results: Among the five candidate regions, the CpG sites in FAM63B and IR on chromosome 16 were significantly hypomethylated in the samples from subjects with BD as well as those from subjects with SZ. On the other hand, the CpG sites in TBC1D22A were hypermethylated in the samples from subjects with BD, in contrast to hypomethylation in the samples from subjects with SZ. Conclusion: Hypomethylation of FAM63B and IR on chromosome 16 could be common epigenetic risk factors for SZ and BD. Further comprehensive epigenetic studies for BD, such as MWAS, will uncover the extent of similarity and uniqueness of epigenetic alterations.